Combining batch experiments and spectroscopy for realistic surface complexation modelling of the sorption of americium, curium, and europium onto muscovite. (1st September 2022) - Bezzina, James P.; Neumann, Julia; Brendler, Vinzenz; Schmidt, Moritz
Highlights: Multi-method approach to study trivalent actinide sorption onto muscovite. First spectroscopic verification of surface species of trivalent actinides on muscovite. Reliable surface complexation model based on spectroscopically verified speciation. Abstract: For a safe enclosure of contaminants, for instance in deep geological repositories of radioactive waste, any processes retarding metal migration are of paramount importance. This study focusses on the sorption of trivalent actinides (Am, Cm) and lanthanides (Eu) to the surface of muscovite, a mica and main component of most crystalline rocks (granites, granodiorites). Batch sorption experiments quantified the retention regarding parameters like pH (varied between 3 and 9), metal concentration (from 0.5 µM Cm to 10 µM Eu), or solid-to-liquid ratio (0.13 and 5.25 g·L −1 ). In addition, time-resolved laser fluorescence spectroscopy (TRLFS) using the actinide Cm(III) identified two distinct inner-sphere surface species. Combining both approaches allowed the development of a robust surface complexation model and the determination of stability constants of the spectroscopically identified species of (S-OH)2 M 3+ (logK o −8.89), (S-O)2 M + (logK o −4.11), and (S-O)2 MOH (logK o −10.6), with all values extrapolated to infinite dilution. The inclusion of these stability constants into thermodynamic databases will improve the prognostic accuracy of lanthanide and actinide transport through groundwater channels in soils and crystalline rock systems. Graphical abstract: Image, graphical abstract